Elevated soluble CD163 predicts renal function deterioration in lupus nephritis: a cohort study in Eastern China - Guangxia Yang (SAGE Publishing, 2021)
Objective This study investigated the association between soluble scavenger receptor differentiation antigen 163 (sCD163) and the severity and prognosis of renal injury in lupus nephritis (LN). Methods Serum sCD163 levels in 121 Eastern Chinese patients with LN who underwent renal biopsy were determined by enzyme-linked immunosorbent assays. Clinical data were collected, and the glomerular filtration rate and disease activity score of lupus were calculated. Pathological classification was performed, and renal pathological scores were assessed by the activity index (AI) and chronic index (CI). Kaplan–Meier survival curves were drawn to evaluate prognosis. Results The pathological classification, AI and CI scores in the high sCD163 group were increased. The sCD163 levels were positively correlated with serum creatinine, blood urea nitrogen, AI scores and CI scores and negatively correlated with the estimated glomerular filtration rate. Kaplan–Meier survival analysis showed that the incidence of renal endpoint events was increased in the high sCD163 group compared with the normal sCD163 group. Conclusion The serum sCD163 level correlates with the severity of LN and is an important indicator of poor renal prognosis in patients with LN.